2021
DOI: 10.1021/acs.jpca.0c09096
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and Photochemistry of Pyruvic Acid at the Air–Water Interface

Abstract: Interfacial regions are unique chemical reaction environments that can promote chemistry not found elsewhere. The air−water interface is ubiquitous in the natural environment in the form of ocean surfaces and aqueous atmospheric aerosols. Here we investigate the chemistry and photochemistry of pyruvic acid (PA), a common environmental species, at the air−water interface and compare it to its aqueous bulk chemistry using two different experimental setups: (1) a Langmuir−Blodgett trough, which models natural wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(75 citation statements)
references
References 125 publications
0
75
0
Order By: Relevance
“…We note that all types of oligomerization reactions, which could be promoted at the surface of water in natural environments, are potentially important for building the chemical complexity required for life. A recent study assessing both the photochemistry and the "dark" (i.e., no irradiation) chemistry of pyruvic acid by Kappes et al 14 at water−air interfaces observed complex oligomeric products at the surface of water under both conditions. The oligomers observed were likely formed by condensation reactions, and, intriguingly, in the case of the dark chemistry, formed spontaneously from a solution of simple monomeric precursors under ambient temperature.…”
Section: Condensation Reactions At the Water−air Interfacementioning
confidence: 99%
See 2 more Smart Citations
“…We note that all types of oligomerization reactions, which could be promoted at the surface of water in natural environments, are potentially important for building the chemical complexity required for life. A recent study assessing both the photochemistry and the "dark" (i.e., no irradiation) chemistry of pyruvic acid by Kappes et al 14 at water−air interfaces observed complex oligomeric products at the surface of water under both conditions. The oligomers observed were likely formed by condensation reactions, and, intriguingly, in the case of the dark chemistry, formed spontaneously from a solution of simple monomeric precursors under ambient temperature.…”
Section: Condensation Reactions At the Water−air Interfacementioning
confidence: 99%
“…We note that while leucine ethyl ester is a small organic molecule that is soluble (and therefore present) in bulk solution, even highly soluble molecules also exhibit some degree of surface activity. 14,31,32 These molecules, aided by the hydrophobic effect, 42,43 partition to the surface, leading to increased concentrations at the air− water interface. Following equilibration, the leucine ethyl ester system showed peptide bond formation, 1 which was detected by a new distinct vibrational feature in the reflection−absorption spectrum at ∼1625 cm −1 corresponding to the Amide I band of a dipeptide.…”
Section: Condensation Reactions At the Water−air Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, experiments using liquid films of PA photolyzed in the presence of a 100 ppb ozone exhibited dominant surface chemistry over that registered in the bulk, pointing out the importance of this heterogeneous process [ 90 ]. Similarly, other attempts have aimed to investigate the m/z value of possible oligomers in heterogeneous chemistry [ 91 , 92 ], although regularly battling with the presence of impurities before starting the reactions.…”
Section: Atmospheric Photochemistry and Small 2-oxocarbxylic Acidsmentioning
confidence: 99%
“…Surface-sampling of Langmuir troughs enables chemical analysis of photochemical products at the liquid interface and in the bulk. 18 Mass spectrometry-based experiments on thin films as well as droplets in microemulsions and the gas phase have shown significantly enhanced surface chemical reaction rates compared to bulk liquids. [19][20][21] Molecular beam scattering, originally developed to probe interactions between pairs of gas-phase molecules 22,23 and gas-phase molecules with solid surfaces, 24,25 has proved to be a direct and powerful means for investigating the dynamics of elementary chemical reactions.…”
Section: Introductionmentioning
confidence: 99%